SOCIAL NETWORK DYNAMICS AND L2 PROFICIENCY: A SOCIOLINGUISTIC ANALYSIS OF LEARNERS IN A SOUTH AFRICAN MULTILINGUAL CONTEXT - Chavalala, Billy James (Universitas Islam Sumatera Utara (UISU), 2025)
This study examined sociolinguistic dimensions of second language acquisition (SLA) within a multilingual community in South Africa, focusing on how social identity, community participation, and cultural context shaped learners’ linguistic development. Employing a mixed-methods ethnographic approach, the research used sociolinguistic surveys and in-depth interviews with second-language learners from diverse linguistic backgrounds to investigate how factors such as social identity, social class, age, gender, and motivational dynamics influenced SLA outcomes. The study further explored how learners navigated sociocultural boundaries within complex multilingual networks and how language attitudes and ideologies informed their engagement with the target language community. Findings revealed that social network integration specifically the frequency and quality of interaction with target-language speakers emerged as the strongest predictor of linguistic proficiency, providing learners with sustained opportunities for meaningful language use. Positive attitudes toward the target language and its speakers were also associated with higher levels of linguistic integration and increased use of the language in everyday contexts. Overall, the research demonstrated that SLA was profoundly shaped by the interplay of social networks, identity positions, and local cultural dynamics. The study underscored the need for pedagogical and policy approaches that strategically promoted learners’ participation in target-language social networks to improve L2 acquisition in diverse multilingual settings.